2017
DOI: 10.1371/journal.pone.0183754
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant chemotherapy and postoperative adjuvant chemotherapy cycles on survival of patients with advanced-stage ovarian cancer

Abstract: BackgroundThere is currently no consensus regarding the optimal number of chemotherapy cycles to be administered before and after interval debulking surgery (IDS) in patients with advanced ovarian cancer. This study aimed to evaluate the impact of the number of neoadjuvant chemotherapy (NAC) and postoperative adjuvant chemotherapy (POAC) cycles on the survival of patients with advanced ovarian cancer undergoing NAC/IDS/POAC.MethodsWe retrospectively reviewed data from 203 patients who underwent NAC/IDS/POAC at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In support of the guidelines, retrospective studies have shown that patients who received extended NACT cycles had worse outcomes [20,21]. However, other studies have reported contradictory results by demonstrating that IDS after ≥ 6 NACT cycles could be safe and help achieve higher complete resection [22][23][24][25]. The biological nature of a tumor acquiring chemotherapy resistance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the guidelines, retrospective studies have shown that patients who received extended NACT cycles had worse outcomes [20,21]. However, other studies have reported contradictory results by demonstrating that IDS after ≥ 6 NACT cycles could be safe and help achieve higher complete resection [22][23][24][25]. The biological nature of a tumor acquiring chemotherapy resistance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main therapeutic strategy for OC patients with early FIGO stage disease is surgical resection; however, due to the high risk of recurrence (25-30%), the majority of patients receive concurrent adjuvant chemotherapy [2,20]. Usually, surgical resection is not curative for patients with advanced stage OC, and postoperative chemotherapy has been widely accepted as the standard for the treatment of advanced OC [21]. Cisplatin, a well-known antitumor agent that was first synthesized in 1844 by M. Peyrone, has been proven to combat miscellaneous tumors, such as breast cancer, lung cancer, and liver cancer, significantly improving the prognosis of cancer patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…After patients were clinically diagnosed as having FIGO stage III or IV, the pathologic diagnosis of epithelial ovarian cancer was made by cytologic evaluation of ascites/pleural effusion, image-guided aspiration biopsy, and diagnostic laparoscopic/laparotomy biopsy. Our institution applied the following selection criteria for the use of NAC as the primary treatment strategy regardless of histologic subtypes: 18 1) pulmonary and/or hepatic parenchymal metastases were observed on initial imaging studies, 2) patients had poor performance status and high operative risk due to medical comorbidities, or 3) optimal debulking surgery (residual disease measuring 1 cm or less) was unsuitable due to high tumor burden (Fagotti score ≥8). 19 …”
Section: Methodsmentioning
confidence: 99%